PENGARUH LIKUIDITAS DAN KUALITAS ASET TERHADAP PERTUMBUHAN LABA PADA BANK UMUM YANG TERDAFTAR DI BEI TAHUN 2013-2015 - Putra, Surya Darma; Jubaedah, Jubaedah (Ekonomi dan Bisnis, 2016)
This research is using quantitative study aimed to see whether there are influence of liquidity and asset quality on growth profit of commercial banks listed on the BEI period 2013-2015. The population in this research using banging company which consist of 41 companies. The total samples used in this research as 36 companies accordance with established criteria, that are Indonesia banking company,to publish financial statement last 3 years, listed on the stock exchange indonesia, and conventional banking. Data used in this research is secondary data obtained from the financial statements. The analytical method used is to combine the data time series and cross section to calculate or estimate the quantitative variables used for stock return. The analysis of panel data regression model with program Eviews 9.0 and level of significance 5% (0,05). The result showed that (1) Liquidty has no significant effect on growth profit, (2) Asset quality has significant on growth profit.